Gyneco-Obstetric risk factors for Fetal Macrosomia in pregnancy at the Gyneco-Obstetrics service of Víctor Ramos Guardia Hospital, Huaraz, Peru - Vasquez-Ortega, Gabriela (2023)
Objective. To determine the relationship between gynecological-obstetric risk factors for fetal macrosomia in pregnant women at the Gynecology-Obstetrics Service of Víctor Ramos Guardia Hospital, Huaraz, during the period 2017-2020. Materials and Methods. The case-control study was conducted at Víctor Ramos Guardia Hospital, Huaraz, during the period 2017-2020. The study population consisted of 10,838 pregnant women who were attended at the Gynecology-Obstetrics Service, with 187 cases and 374 controls. A documentary analysis was performed. Data collection was done using a data collection form validated by experts in the fields of methodology, statistics, and Gynecology-Obstetrics specialists. The data were extrapolated to SPSS version 25 database. Chi-square tests and logistic regression were applied. Results. Regarding the clinical characteristics of the mothers, the following data were observed: 15.6% of the mothers were aged over 35 years, 32.2% were overweight, 1.6% had a history of macrosomia, 27% had a history of multiparity, 0.5% had gestational diabetes, 51.3% had a male fetus, and 2.4% experienced excessive weight gain. The prevalence of macrosomia was 2.6%. Several significant risk factors (p<0.05) associated with fetal macrosomia were identified: pregestational diabetes (OR=6.16), obesity (OR=2.34), history of macrosomic child (OR=9.03), excessive weight gain (OR=25.834), gestational diabetes (OR=9.84), and male fetal sex (OR=1.52). Conclusion. A significant association was found between various risk factors and fetal macrosomia in pregnant women. These risk factors included pregestational diabetes, obesity, history of macrosomic child, excessive weight gain, gestational diabetes, and male fetal sex.